(untitled) (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2025)
This study aims to analyze the impact of Islamic education policy on the quality of education in Indonesia. The policy covers teaching methods, curriculum design, and educational practices in Islamic institutions, with the goal of fostering balanced religious understanding, moral integrity, psychological growth, and respect for social diversity. Using a qualitative literature review, the research finds that the policy affects curriculum alignment with national standards, professional development and recruitment of educators, allocation of funding, teacher welfare programs, and institutional governance systems. However, the existence of dual authority between the Ministry of Religious Affairs and the Ministry of Education often results in overlapping responsibilities, inconsistent regulations, and unequal distribution of resources. These issues contribute to significant disparities in the quality and accessibility of Islamic education services across different regions.